Treatment of myelin oligodendrocyte glycoprotein immunoglobulin G–associated disease. Issue 1 (17th February 2021) - Healy, Sarah; Elhadd, Kariem Tarik; Gibbons, Emily; Whittam, Dan; Griffiths, Michael; Jacob, Anu; Huda, Saif
Abstract: Myelin oligodendrocyte glycoprotein (MOG) immunoglobulin G (IgG)–associated disease (MOGAD) is increasingly recognized as a distinct nosological entity from aquaporin‐4 antibody IgG–positive neuromyelitis optica spectrum disorder (AQP4‐IgG NMOSD). The advent of highly specific MOG‐IgG cell‐based diagnostic assays have helped to refine our understanding of the clinical spectrum of MOGAD. To date, treatment approaches have been largely extrapolated from AQP4‐IgG NMOSD experience, but there is growing evidence of distinct differences in treatment response between these conditions. This review summarizes the current status and understanding of acute and chronic treatments for MOGAD. Timing and duration of treatment, pregnancy, and emerging therapies are also discussed. Abstract : This review summarizes the current understanding of acute and chronic treatments for MOGAD. Timing and duration of treatment, pregnancy, and emerging therapies are also discussed.